The best Christmas ever - Green, Sylvia; Chapman, Chris (New York : Scholastic, 2001)
Puss, a cat, runs away from his owner in order to escape from the city and return to the country, but later changes his mind-- just in time for Christmas.
"A little Apple paperback."
5.2
3-6
3-6
500
Keywords: Cats -- Fiction; Christmas -- Fiction; City and town life -- Fiction; Country life -- Fiction; Cats -- Fiction; Christmas -- Fiction; City and town life -- Fiction; Country life -- Fiction